Karen Barad as Educator: Agential Realism and Education - Du Preez, Petro (Critical Studies in Teaching and Learning, 2023)
Murris, K. 2022. Karen Barad as Educator: Agential Realism and Education. Singapore: Springer Nature Singapore Ptd Ltd. What do the tracing of stories about plastic bricks, the moon, an aquarium, Zuko, a pregnant stingray, Facebook, a stick, ghosts, and many other kin, have in common? And, how might ‘[a]rticulating those stories ...help “stretch” our response-ability as educators to includeallhumans and other-than-humans as part of our earthly survival and more just futures’(Murris, 2022:18). And, ‘[w]hat on earth (and beyond) could quantum physics teach educators?’(Murris, 2022:6).